From amateur to professional cycling: A case study on the training characteristics of a zwift academy winner - Gotti, D.; Codella, R.; Vergallito, L.; Meloni, A.; Arrighi, T.; La Torre, A.; Filipas, L. (Sports, 2025)
This study aimed to describe the training leading to the Zwift Academy (ZA) Finals of a world-class road cyclist who earned a professional contract after winning the contest. Four years of daily power meter data were analyzed (male, 25 years old, 68 kg, VO2max: 85 mL·min-1·kg-1, and 20-min power: 6.37 W·kg-1), focusing on load, volume, intensity, and strategies. Early training alternated between long, moderate-intensity sessions and shorter high-intensity sessions, with easy days in between. Gradually, the structure was progressively modified by increasing the duration of moderate-intensity (MIT) and high-intensity (HIT) and, subsequently, moving them to "high-volume days", creating a sort of "all-in days" with low-intensity (LIT), MIT, and HIT. Moderate use of indoor training and a few double low-volume, low-intensity sessions were noted. These data provide a deep view of a 4-year preparation period of ZA, providing suggestions for talent identification and training, thereby highlighting the importance of gradual progression in MIT and HIT.